PENGARUH KOMUNIKASI WORD OF MOUTH DAN PERSONAL SELLING TERHADAP KEPUTUSAN MELAKUKAN SIMPAN PINJAM DI BUMDES SEROJA KABUPATEN KUANTAN SINGINGI - Anisa Vebriyanti Solehah; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Word of mouth communication is the private discussion of a product between potential customers, friends, family, coworkers, and colleagues. Personal selling is an oral presentation by a company or institution to one or more potential customers with the aim of selling the goods or services offered. Marketing communication within an institution, such as BUMDes, is an important aspect of the overall content of marketing. The theory used in this study is the S-R (Stimulus-Response) theory. The study aims to determine the influence of word of mouth communication and personal selling on customers' decisions to make savings and loans at village-owned enterprises (BUMDes) Seroja, Kuantan Singingi district. Explanative quantitative methods were used in this study, and data were collected through the distribution of questionnaires to 150 respondents to BUMDes seroja. The results of the study using the SPSS test indicated that the partial test of word of mouth had a t-value of 7.492 with a significant level of 0.000, and the personal selling partial test had a t-value of 4.54 with a significant level of 0.000. The coefficient of determination (R2) obtained an Adjusted R Square value of 0.489, indicating that the percentage of influence of the independent variables word of mouth and personal selling on the dependent variable on savings and loan decisions was 48.9%, classified as a moderate level of influence. However, 51.1% was influenced by other variables not examined in this study. Keywords: Word Of Mouth Communication, Personal Selling,Purchase Decision